2012
DOI: 10.1371/journal.pone.0035186
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of a Series of 2-Substituted-5-Thiopropylpiperazine (Piperidine)-1,3,4-Oxadiazoles Derivatives as Atypical Antipsychotics

Abstract: BackgroundIt is important to develop novel antipsychotics that can effectively treat schizophrenia with minor side-effects. The aim of our work is to develop novel antipsychotics that act on dopamine D2 and D3, serotonin 5-HT1A and 5-HT2A receptors with low affinity for the serotonin 5-HT2C and H1 receptors, which can effectively cure positive symptoms, negative symptoms and cognitive impairment without the weight gain side-effect.Methodology/Principal FindingsA series of 2-substituted-5-thiopropylpiperazine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…It should be noted that (6‐fluorobenzo[d]isoxazol‐3‐yl)piperidine derivative 5 displayed high affinities for the D 2 and 5‐HT 2A receptors (D 2 K i = 11.9 nM; 5‐HT 2A K i = 7.5 nM). These results also indicated that compounds bearing a 6‐fluorobenzo[d]isoxazol‐3‐yl)piperidine moiety ( 5 ) showed higher affinities to two receptors than those with a (benzo[d]isothiazol‐3‐yl)piperazine fragment ( 6 ) 30. Compound 15 bearing 2‐(piperidin‐4‐yl)benzo[d]oxazole showed low affinities for the D 2 and 5‐HT 2A receptors ( K i > 10 000 nM).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…It should be noted that (6‐fluorobenzo[d]isoxazol‐3‐yl)piperidine derivative 5 displayed high affinities for the D 2 and 5‐HT 2A receptors (D 2 K i = 11.9 nM; 5‐HT 2A K i = 7.5 nM). These results also indicated that compounds bearing a 6‐fluorobenzo[d]isoxazol‐3‐yl)piperidine moiety ( 5 ) showed higher affinities to two receptors than those with a (benzo[d]isothiazol‐3‐yl)piperazine fragment ( 6 ) 30. Compound 15 bearing 2‐(piperidin‐4‐yl)benzo[d]oxazole showed low affinities for the D 2 and 5‐HT 2A receptors ( K i > 10 000 nM).…”
Section: Resultsmentioning
confidence: 82%
“…In fact, some of the latest efforts in the development of novel antipsychotic drugs are aimed at obtaining compounds with binding affinities for a certain number of receptors 10, 27–30. In this paper, we describe our recent efforts to discover novel antipsychotic agents with a piperidine‐2,6‐dione system linked to the arylpiperazine (piperidine) group, which is one of the most important classes for CNS activity 31–33.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 H]8‐OH‐DPAT (187.4 Ci/mmol, Perkin Elmer Life Sciences) was used for labeling the 5‐HT 1A receptor. The assay was carried out according to the previously published procedure . Rat cerebral cortex was homogenized in 20 volumes of ice‐cold Tris–HCl buffer (50 mM, pH 7.7) using an ULTRA TURRAX homogenizer, and was then centrifuged at 32,000 g for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Heterocyclic compounds forms the backbone for the discovery of many bioactive compounds. Chemical literature survey reveals that piperazine derivatives are biologically versatile compounds which possess potent antifungal [1,2], antimicrobial [3,4], antihistamine [5], antipsychotic [6,7], anticonvulsant [8][9][10] properties.…”
Section: Introductionmentioning
confidence: 99%